Reactions to driving cessation: a qualitative study of people with dementia and their families. (October 2015) - Chacko, Emme Elizabeth; Wright, Wendy Margaret; Worrall, Richard Charles; Adamson, Carole; Cheung, Gary
Objectives: A proportion of older people with mild dementia are safe to drive. However, driving cessation is recommended at some point as the disease progresses. Driving cessation can have significant psychological and social consequences on people with dementia and their carers. This paper aims to explore the psychosocial and adjustment issues following driving cessation for people with dementia and their supporters. Method: Participants and their supporters were interviewed within 1 month of driving-cessation advice, and again 6 months later. Issues associated with driving cessation were explored in semi-structured interviews. Results: Seven participants and their supporters were recruited. This has generated a total of 22 transcripts for qualitative analysis including follow-up interviews. For those who could remember the details of driving cessation, most were unhappy with the decision. Carers who were supportive of driving cessation questioned the legality of it. Most participants minimised the impact of their driving cessation on their supporters. Most supporters were negatively affected by the decision. Conclusions: The preliminary findings highlight the need for a more comprehensive process for driving cessation in those with dementia, with closer links to regulatory bodies, and increased support for their families/carers.